Effect of different illumination patterns on the growth and biomolecular synthesis of isolated Chlorella Thermophila in a 50 L pilot-scale photobioreactor. (October 2021) - Sarkar, Sambit; Manna, Mriganka Sekhar; Bhowmick, Tridib Kumar; Gayen, Kalyan
Graphical abstract: Highlights: Light/dark ratio plays a vital role in growth and biomolecule synthesis. Continuous lighting wasn't preferred for the growth of Chlorella Thermophila . Sinusoidal lighting with light/dark ratio showed higher protein synthesis. Continuos lighting enhanced carotenoids and carbohydrate accumulation. Economic analysis showed a potential profit of 43 %. Abstract: Optimum light exposure for the cultivation of microalgae to obtain high biomass density varies between different species. In the current work, isolated microalgae strain Chlorella thermophila was used to investigate the growth and biomolecular content under exposure of various light regimes in a pilot-scale flat plate photobioreactor (50 L). Here, three different lighting patterns namely fixed (4500 lx intensity with 14:10 light/dark ratio), variable (0−4500 lux variable intensity with 14:10 light/dark ratio) and continuous mode (4500 lx intensity with 24:0 light/dark ratio) were studied for the evaluation of the importance of light/dark period and sinusoidal illumination. Results demonstrated that the light/dark period had a significant influence on the growth and synthesis of biomolecules. The biomass concentration at fixed mode was found to be 5.6 and 1.9 fold higher compared to continuous mode and variable mode, respectively. Chlorophyll content was found to be the highest (4.8 %, w/w) in fixed mode while protein content was highest (68 %, w/w) in variable mode. The highest content of carotenoids (0.69 %, w/w) and carbohydrates (38 %, w/w) were noticed in continuous lighting mode. The highest average productivity of 16.4, 10.5, 4.03, 0.76, 0.6 (mg/L.day) were achieved for biomass, proteins, carbohydrate, chlorophylls and carotenoids, respectively in fixed mode.